Electrocardiogram and arrhythmias. Issue 5 (May 2015) - Singh, Rajender; Murphy, Jeremy J.
Abstract Introduced by Einthoven, electrocardiography remains the most common diagnostic procedure readily available to the physician in primary and secondary care. It is a graphical display of the electrical potential difference as it spreads through the heart and is recorded at the body surface. The electrocardiogram (ECG) is an indispensable tool to screen and monitor cardiac patients. Exercise ECG is used to diagnose coronary artery disease and ambulatory ECG to assess arrhythmias.